Gereja Katolik dan Orang Cacat Mewujudkan Mimpi Gereja Kaum Miskin - Yosef Masan Toron (STIPAS St. Sirilus Ruteng, 2012)
The identity of the church is nothing else that a proclaimer or a person in dialogue, a friend of all. Dialogue with poverty is for Jesus mutual communing with people who are poor and marginalized.The article shows us how the church seeks equal status with persons to whom she brings the proclamation. The approach is never done from the post of superiority.The church should pass the first step that is humility in proclaiming the good news.People listen to the men who is mercifull not to the intricacies of the doctrinal teaching,the crowd watcher for the compassionate person, the one who knows pity and sympathy. Life of compassion is an important ministry in the church.Compassin should become part of life for the church and compassion transcends barriers of any kind.